The association between serum uric acid and depression among U.S. National Health and Nutrition Examination Survey - He, Hong; Li, Ping; Huang, Haokun; Zeng, Yanlin; Zhang, Min; Chen, Zhibing; Huang, Shiqi; Zeng, Fangfang; Ge, Hui (Frontiers in Nutrition, 2025)
BackgroundPrevious studies have suggested that serum uric acid (UA) may influence depression through oxidative stress pathways, but with inconclusive results. This study aimed to investigate the association between serum UA levels and depression, as well as potential variations across demographic subgroups in the U.S. adult population.MethodsA cross-sectional analysis of 23,059 participants from NHANES (2013–2018) was conducted. Serum UA levels were classified into quartiles, and depression was measured using the Patient Health Questionnaire-9 (PHQ-9), with a score ≥ 10 indicating depression. Weighted logistic regression models were used to analyze the association between UA levels and depression, adjusting for demographic and clinical covariates. Subgroup analyses were performed to assess variations by sex, age, race/ethnicity, and other health-related factors.ResultsParticipants in the highest UA quartile had a lower prevalence of depression compared to those in the lowest quartile (13.9% vs. 16.2%, p = 0.004). After adjusting for covariates, higher UA levels were significantly associated with a reduced risk of depression (OR = 0.76, 95% CI: 0.67, 0.86, p < 0.001 for quartile 4). Subgroup analyses indicated significant interactions by age (p for interaction = 0.051), race/ethnicity (p for interaction = 0.027), and history of cardiovascular disease (p for interaction = 0.005), with more pronounced inverse associations observed among older adults, other races and participants with cardiovascular disease.ConclusionHigher serum UA levels were inversely associated with depression among U.S. adults, especially among races, participants with cardiovascular disease and older age. Further research is needed to confirm these findings and investigate potential underlying mechanisms.